Enhanced Magnetic Anisotropy and Orbital Symmetry Breaking in Manganite Heterostructures. (19th December 2019) - Chen, Pingfan; Huang, Zhen; Li, Mengsha; Yu, Xiaojiang; Wu, Xiaohan; Li, Changjian; Bao, Nina; Zeng, Shengwei; Yang, Ping; Qu, Lili; Chen, Jingsheng; Ding, Jun; et al.
Abstract: Manipulating magnetic anisotropy in complex oxide heterostructures has attracted much attention. Here, three interface‐engineering approaches are applied to address two general issues with controlling magnetic anisotropy in the La2/3 Sr1/3 MnO3 heterostructure. One is the paradox arising from the competition between Mn3d –O2p orbital hybridization and MnO6 crystal field. The other is the interfacial region where the nonuniform MnO bond length d and MnOMn bond angle θ disturb the structural modulation. When the interfacial region is suppressed in the interface‐engineered samples, the lateral magnetic anisotropy energy is increased eighteen times. The d ‐mediated anisotropic crystal filed that overwhelms the orbital hybridization causes the lateral symmetry breaking of the Mn 3d x 2 − y 2 orbital, resulting in enhanced magnetic anisotropy. This is different from the classic Jahn–Teller effect where the lateral symmetry is always preserved. Moreover, the quantitative analysis on X‐ray linear dichroism data suggests a direct correlation between Mn 3d x 2 − y 2 orbital symmetry breaking and magnetic anisotropy energy. The findings not only advance the understanding of magnetic anisotropy in manganite heterostructures but also can be extended to other complex oxides and perovskite materials with correlated degrees of freedom. Abstract : Lateral magnetic anisotropy energy in La2/3 Sr1/3 MnO3 layers is tunable via three different interface‐engineering approaches. The interface‐engineered samples show a uniform MnOMn bond angle and MnO bond length across the entire layer. The direct correlation between 3d x 2 − y 2 orbital symmetry breaking and lateral magnetic anisotropy energy is unveiled, where the dominant role of the crystal field is highlighted.